Bridging CLIL and CALLA for English Academic Writing in Chinese Universities: A Critical Synthesis and the Metacognitive Academic Writing Model - Zhang, Runqiao; Tahir, Mohd Haniff Bin Mohd (Journal of Cultural Analysis and Social Change, 2025)
This narrative review synthesizes theoretical frameworks and empirical evidence to address persistent challenges in academic writing instruction for Chinese university EFL learners. Despite extensive English education, Chinese students struggle with extended academic writing, particularly when managing disciplinary content alongside language production. The review identifies constraints at linguistic, cognitive, and cultural-rhetorical levels, compounded by systemic issues including assessment misalignment and inadequate teacher preparation. The review advances a Metacognitive CLIL orientation that integrates three established traditions: Content and Language Integrated Learning for authentic purposes, the Cognitive Academic Language Learning Approach for explicit strategy instruction, and self-regulated learning for metacognitive development. This framework maps Coyle's Language Triptych directly to genre-specific moves while embedding planning, monitoring, and evaluation as routine lesson components rather than supplementary additions. The contribution is a theoretically coherent framework that addresses the fragmentation characterizing current practice, where content, strategies, and metacognition are treated separately. By providing operational principles for aligning content objectives, genre expectations, and process regulation, the framework offers practical guidance for curriculum design in Chinese universities. The research agenda prioritizes mixed-method evaluations capturing both writing products and composing processes to validate the integrated approach.